2009
DOI: 10.1111/j.1469-0691.2008.02652.x
|View full text |Cite
|
Sign up to set email alerts
|

Nasal carriage of Staphylococcus aureus, including community-associated methicillin-resistant strains, in Queensland adults

Abstract: Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) infections are emerging in southeast Queensland, Australia, but the incidence of carriage of CA-MRSA strains is unknown. The aim of this study was to assess the nasal carriage rate of S. aureus, including CA-MRSA strains, in the general adult population of southeast Queensland. 396 patients presenting to general practices in two Brisbane suburbs and 303 volunteers randomly selected from the electoral rolls in the same suburbs completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
69
7
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 31 publications
15
69
7
5
Order By: Relevance
“…The association between PVL and young age has also been noted by other investigators [29,31,37]. Possible explanations include age-related acquisition of PVL-specific immunity.…”
Section: Discussionsupporting
confidence: 73%
“…The association between PVL and young age has also been noted by other investigators [29,31,37]. Possible explanations include age-related acquisition of PVL-specific immunity.…”
Section: Discussionsupporting
confidence: 73%
“…In previous studies from the central regions of Iran, which showed the closest findings to ours, Erami et al from Kashan city and Khorvash et al from Isfahan city reported a prevalence of S. aureus healthy carriage at 26.3% and 26.6%, respectively (1,12). In some studies conducted among healthcare workers and healthy people from other parts of the world, the nasal carriage rates of S. aureus were reported to be in the range of 18% to 29% (2,5,6).…”
Section: Discussionsupporting
confidence: 66%
“…En el presente estudio se halló una frecuencia de 24,6% de portadores nasales de S. aureus; similar a los resultados obtenidos por diversos autores (23,24) . Luego del análisis estadístico, se encontró que el factor asociado a la colonización por S. aureus fue la edad, específicamente en el rango de 1 a 11 años.…”
Section: Discussionunclassified
“…En cuanto a la edad y el estado portador, se halló una relación inversamente proporcional, la cual es congruente con lo descrito en la literatura (24,25) . Sin embargo, existe una serie de estudios en población adulta mayor, residentes de casas de reposo, en las que la prevalencia de portadores varía entre 20 a 30% (26,27) , por lo que la distribución de portadores en comunidad se comportaría como una distribución bimodal, no observada en el estudio.…”
Section: Discussionunclassified